Zoning of Social Vulnerability for Tidal Flood Disaster in Medan Belawan District, Medan City Based on Remote Sensing and Geographic Information Systems - Budi Rahmah Panjaitan; Lili Somantri; Eka Wulan Safriani; Arifin (United Kingdom) (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2023)
This study aims to 1) identify the social vulnerability of tidal floods in Medan Belawan District and 2) produce a zoning map of social vulnerability to tidal floods in Medan Belawan District descriptive quantitative type research. The variable used refers to Regulation of the Head of BNPB No. 2 of 2012 with changes covering population density, sex ratio, ratio of persons with disabilities, land use, and existing tidal flooding. The social vulnerability variable is then classified using a scoring technique. Data collection techniques in this study were document studies of secondary data obtained from various agencies. The results showed that five urban villages (83%) in Medan Belawan District had high tidal flood social vulnerability, and only one urban town (17%) was classified as having moderate social vulnerability. The urban villages with high tidal flood social vulnerability are Bagan Deli urban village, Belawan Bahagia urban village, Belawan Bahari urban village, Belawan I urban village, and Belawan II urban village. Meanwhile, the urban village with a moderate level of social vulnerability to tidal floods is the Belawan Sicanang Village. Belawan I Village occupies the highest tidal flood social vulnerability class, and the lowest tidal flood social vulnerability class is populated by Belawan Sicanang urban village.Keywords: Social Vulnerability, Tidal Flood, DisasterÂ